Analisis Rasio Keuangan Camel Terhadap Prediksi Kepailitan: Bank Umum Swasta Nasional di Indonesia Periode 2004 – 2007 - Budiwati, Hesti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2011)
The challenge of the banking sector in the future will be more severe, most of which are perceived as a failure of risk management in managing risk can lead to bankruptcy. CAMEL financial ratio analysis can be used as an early warning system of bankruptcy. The purpose of this study are: 1) to obtain empirical evidence regarding differences in financial ratios simultaneously CAMEL significant between bankrupt and insolvent banks, 2) to obtain empirical evidence regarding differences in financial ratios partially CAMEL significant between bankrupt and insolvent banks, 3) to obtain empirical evidence regarding the dominant CAMEL financial ratio in differentiating the bank bankrupt and not bankrupt and 4) to determine the ability of the prediction of several variables distinguishing the CAMEL financial ratios in predicting bankruptcy. Based on the purpose of this study include explanatory research to test the ability of CAMEL financial ratio of CAR, KP, APYD, APYDAP, NPA, PPAP, ROA, ROE, NIM, BOPO, the FBI and the LDR, in predicting bankruptcy in the National Private Banks in Indonesia period 2004 to 2007. The financial statements are used for bank bankruptcy is a two-year financial statements before the bankruptcy, while for banks that do not fit with the bankrupt bank's financial reporting period of bankruptcy. Analysis tools used to test the hypothesis is discriminant analysis using the direct method. The results showed: 1) CAMEL financial ratio to simultaneously have a significant difference between bankrupt and insolvent banks, 2) CAMEL financial ratio that have significant differences between the bank's partial bankruptcy and no bankruptcy is PPAP, ROE, NIM, BOPO and LD, 3 ) CAMEL financial ratio in the aspect of profitability (earnings) ratio of the NIM is the dominant bank in distinguishing bankrupt and not bankrupt, 4) The prediction of several variables distinguishing the CAMEL financial ratio can be used to accurately predict bankruptcy and stable. Other results obtained from this research is by using a model of the cut-off point, the discriminant function generated by CAMEL financial ratio to predict bank is able to distinguish who is in financial trouble.